Skylines [videorecording (DVD)] - Cosmo, James; Bernhardt, Daniel; Ruhian, Yayan, 1968-; Howard, Jonathan (Actor); Jean, Samantha; O'Donnell, Liam, 1982- (Lionsgate, 2021)
When a virus threatens to turn the now earth-dwelling friendly alien hybrids against humans, Captain Rose Corley must lead a team of elite mercenaries on a mission to the alien world in order to save what's left of humanity.